PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2017-2019 - Komang Sutriasa Triafna; Ni Nyoman Sri Rahayu Trisna Dewi; Laras Oktaviani (Universitas Triatma Mulya, 2022)
The population in this research were all banking companies listed on the Indonesia Stock Exchange for the 2017-2019 period, amounting to 43 companies. In this research, the sampling technique was carried out using a purposive sampling method, with a total sample of 28 banking companies during 2017-2019. This research uses multiple linear regression analysis. The results of this research indicate that Value Added Capital Employed (VACA) and Value Added Human Capital (VAHU) have no significant effect on company profitability. Meanwhile, Structural Capital Value Added (STVA), Board of Directors, Board of Independent Commissioners, Managerial Ownership, and Institutional Ownership have a positive and significant impact on the profitability of banking companies. Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Board of Directors, Board of Independent Commissioners, Institutional Ownership, and Managerial Ownership simultaneously have a positive and significant impact on the profitability of banking companies.